FACTORS ASSOCIATED WITH ELDERLY’S SATISFACTION IN INTEGRATED HEALTH SERVICE POST IN VILLAGE TOBIMEITA DISTRICT OF NAMBO CITY OF KENDARI: Elderly's Satisfaction - Sartini Risky MS; Dewi Sari Pratiwi; Muhammad Ikhsan Akbar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Based on the results of interviews with researchers, six out of ten elderly said they were not satisfied with the service because the starting time for integrated post services was sometimes late, the lack of information obtained was related to elderly integrated service post activities. First person said he was satisfied with the service but still complained about the irregular timing of the integrated service post activities. Research is aimed to determine Factors-Factors Associated With Satisfaction Elderly In Integrated Service Post In Village Tobimeita District of Nambo city of Kendari. Methods: This type of research uses research quantitative design with cross-sectional study population of fifty six people. Sampling using purposive sampling with a sample size of fifty six respondents. The data is processed by using a test Fisher's exact test and continued with the test Coefficient Phi. Result: Based on the results of statistical tests there is a strong relationship between service quality and the level of satisfaction of the elderly with p value 0.000 < ? 0.05 , there is a moderate relationship between service and the satisfaction level of the elderly with p value 0.000 < ? 0.05, and there is a strong relationship between the attitude of officers with elderly satisfaction level p value 0.000 < ? 0.05. Conclusion: Researchers suggest that active remind and motivate the elderly to follow integrated service post elderly, other than that in running its role officers also should have to be friendly to the elderly so that the elderly feel happy to follow integrated service post elderly.